Genotypic differences in symbiotic nitrogen fixation ability and seed yield of climbing bean - Barbosa Torres, Norma Constanza; Portilla, Elizabeth; Buendía Castellanos, Hector F.; Raatz, Bodo; Beebe, Stephen E.; Rao, Idupulapati M. (Springer, 2018)
Symbiotic nitrogen fixation (SNF) contributes to improve grain yield under nitrogen (N) deficiency. Climbing beans are known to be superior to bush beans in their potential for SNF. The main objectives of this study were to: (i) quantify genotypic differences in SNF ability of climbing beans using 15N natural abundance method; (ii) identify climbing bean genotypes that combine high SNF ability with high yield potential that could serve as parents in the breeding program; and (iii) test whether δ15N in seed can be used instead of δ15N in shoot for estimating SNF ability.